Maybe - Yamada, Kobi; Barouch, Gabriella, 1985- (Seattle, WA : Compendium, Inc., 2019)
You are the only you there every has been or ever will be. You are unique. Just the odds of you being here at this exact place and this exact time are so great and so rare that they will never happen again. This is a story for everything you will do and everything you could be. It's for who you are right now, and it's for all the magical, unbounded potential you hold inside.
Booklist, July 2019
Kirkus Review, June 2019
School Library Journal, August 2019
2.2
K-3
A story about the endless potential in all of us - Cover.
Keywords: Self-actualization (Psychology) -- Juvenile fiction; Creative ability -- Juvenile fiction; Self-actualization (Psychology) -- Fiction; Creative ability -- Fiction; Identity -- Fiction; Self-realization -- Juvenile fiction